EFEKTIFITAS INTERNET BASE COGNITIVE BEHAVIORAL THERAPY PADA GANGGUAN KECEMASAN: LITERATURE REVIEW - Ida Ayu Trisnadewi (Coping: Community of Publishing in Nursing, 2021)
Anxiety disorders are the most common of mental disorders and affect nearly 30 percent of adults at some point in their lives. iCBT (Internet Base Cognitive Behavioral Therapy) is an effective, easy-to-accept and practical health care in health care for anxiety disorders. The purpose of this study was to determine the effectiveness of Internet Base Cognitive Behavioral Therapy on anxiety disorders. The research method of this study uses non-Systematic Review Literature Review. The literature in this study was obtained through the online databases EBSCOHost, SpingerLink, Willey, ScienceDirect and ProQuest published from 2016 to 2021. Based on an analysis of the journals obtained, Internet Base Cognitive Behavioral Therapy has proven to be effective and cost-effective for use in the management of anxiety disorders. Mobile applications in smartphones are the most popular because of the convenience they provide. The use of iCBT will be more effective in its implementation with professional support from service providers.